GAYA HIDUP HEDONISME DALAM KONSUMSI DITINJAU DARI PERSPEKTIF EKONOMI ISLAM (Pada Mahasiswi Jurusan Ekonomi Islam IAIN Kota Bengkulu) - Mardian Suryani; Siti Achiria (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
A hedonic lifestyle is a lifestyle that prioritizes mere pleasure. Many individuals have a hedonic lifestyle, including students. The purpose of this study is to find out what are the factors that lead to the hedonism lifestyle of the students of the Islamic Economics Department of IAIN, Bengkulu City, and how to review the Islamic Economy on Hedonism Behavior. This research is a qualitative research, with a phenomenology approach. Using a purposive sampling technique involving the 4th semester students and 6th semester students. The results showed that the factors that influence the lifestyle of hedois for female students in economics majors in general are divided into two, namely (internal), and (external) factors. Islam does not justify a hedonic lifestyle because it will cause harm to individuals and society, where a lifestyle like this will lead to a spree in which Islam teaches life according to needs (maslahah) a hedonic lifestyle will give youth a disadvantage, in this case college student.